How much do people spend on physical activity in England: a nationwide cross-sectional survey of expenditure. (November 2016) - Anokye, Nana Kwame; Pokhrel, Subhash; Doyle-Francis, Melanie; Fox-Rushby, Julia
Abstract: Background: Priced-based policies (eg, the new UK sugar tax) are an important tool for public health. Spending on physical activity might be a barrier for participation. However, little is known about the level of expenditure, its correlates, and potential for health policies. We assessed nationwide expenditure patterns on physical activity in England, the processes in individuals' decision making, and policy implications. Methods: Participants were from a 2010 telephone survey of a representative sample of adults nationwide (≥16 years old) who did sports and exercise in the Health Survey for England 2008 and agreed to be re-contacted. We invited 3130 adults using stratified two-stage random sampling (households and then individuals) to allow interview of one person per household and control for any household interaction effect. Interviews covered types and frequency of sports and exercise expenditure, frequency and intensity of activity, and individual characteristics. A two-part regression model was fitted to explain the decision to spend on sports and exercise and level of expenditure. Findings: Of 1686 respondents (56% response rate), 1393 (83%) had undertaken sports and exercise via 72 activities. 710 (51%) were women, 821 (59%) were aged 45 years or older, 864 (62%) were employed, and 237 (17%) had an annual household income above £46 800. Popular activities were working out (n=534, 38%), swimming (362, 26%), cycling (344, 25%), running (319, 23%), and walking (231, 17%). 957 (69%) of 1393 sports and exercise participants spent money to do so (mean expenditure per month £176, SD 912). Most frequent expenses were fees for membership, competition, and classes, and this expenditure rose with activity. The decision to spend was related to older age (β coefficient −0·788), high income (0·733), being single (0·428), and not smoking (0·575), whereas level of expenditure was associated with low educational qualification (0·378), high income (0·471), households with at least one child (one child −0·524, two children −0·511, three or more children −0·522), and being resident in south and central England (0·542). Interpretation: This study confirms that whether and how much to spend money on sports and exercise are two separate decisions that are associated with different sets of predictors. Proposals for price-based policies on physical activity in the UK need to consider this subtle difference in individual behaviour, either by targeting specific groups (eg, spenders on sports and exercise) or by implementing wider environmental interventions for non-spenders. Funding: Department of Health's Policy Research Programme (England).